Basic‐Level Categories, Mirror Neurons, and Joint‐Attention Schemes: Three Points of Intersection Between G.H. Mead and Cognitive Science. Issue 1 (1st October 2015) - McVeigh, Ryan
Abstract : Recent research in cognitive science has provided broad empirical support for the model of cognition and self‐development formulated by G.H. Mead. This is demonstrated specifically through three distinct cognitive mechanisms: basic‐level categories, mirror neurons, and joint‐attention schemes. These mechanisms illustrate a form of embodied sociality that underscores the intersubjective foundation of mind and self articulated by Mead. Research on basic‐level categories, mirror neurons, and joint‐attention schemes further extends Mead's relevance outside standard sociological and social psychological circles to the field of cognitive science and its emerging focus on sociality and social interaction.